(3eTGQb CfhGQ Gdjbjf aj MbGFb CSQGQ CejQ GdeDefjfs - (3GdMGaX GdHQSjs ((3YHO GdQGRb GdJHQjRi s)
(3ChdgG (B:s
(3GdMeO ddg GdeJaQO HGdCRd GdCHO jbhd GdhGKb HGdaQO GdUeO GdMGaX GdHQSi EYdehG Cf HYV GdMGSOjf GdPjf djS dge MX ai GdOjf s
(3BNQgG (B:s
(3VdGdi Cf MHi dYdi GdeQJVi Yjf ceG di hgh QGOi ai eYGOi hNdai ai eGdi hHg cedJ Ojfi hHg NJe ebGdi JeJ GdQSGdI eTGQb CfhGQ Gdjbjf HYhf Gddg Gdedc GdMb GdeHjf s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs